2014
DOI: 10.1371/journal.pone.0085882
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-21 Is a Critical Regulator of CD4 and CD8 T Cell Survival during Priming under Interleukin-2 Deprivation Conditions

Abstract: Optimal T cell activation and expansion require binding of the common gamma-chain (γc) cytokine Interleukin-2 (IL-2) to its cognate receptor that in turn engages a γc/Janus tyrosine kinase (Jak)3 signaling pathway. Because of its restricted expression by antigen-activated T cells and its obligatory role in promoting their survival and proliferation, IL-2 has been considered as a selective therapeutic target for preventing T cell mediated diseases. However, in order to further explore IL-2 targeted therapy, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
2
9
1
Order By: Relevance
“…Data from our laboratory recently showed that IL-21 was up-regulated during the peak of the effector CD8 T cell immune response to E. cuniculi infection and absence of signaling for this cytokine led to impaired CD8 T cell immunity (manuscript under preparation). Our findings are supported by recent observations, which demonstrated that under IL-2 deprivation conditions, IL-21 might act as the major survival factor promoting the T cell immune response [53]. In addition, it has been reported that IL-21 can synergize with two other common gamma chain members, IL-7 and IL-15, in order to promote expansion and in some cases anti tumor functions of CD8 T cells [54,55].…”
Section: Role Of Cd4 Help In the Development Of Cd8 T Cell Immunity Asupporting
confidence: 90%
“…Data from our laboratory recently showed that IL-21 was up-regulated during the peak of the effector CD8 T cell immune response to E. cuniculi infection and absence of signaling for this cytokine led to impaired CD8 T cell immunity (manuscript under preparation). Our findings are supported by recent observations, which demonstrated that under IL-2 deprivation conditions, IL-21 might act as the major survival factor promoting the T cell immune response [53]. In addition, it has been reported that IL-21 can synergize with two other common gamma chain members, IL-7 and IL-15, in order to promote expansion and in some cases anti tumor functions of CD8 T cells [54,55].…”
Section: Role Of Cd4 Help In the Development Of Cd8 T Cell Immunity Asupporting
confidence: 90%
“…2G). Importantly, we did not observe a correlation between production of IL-2 by CD4 T cells and IL-21 by CD8 T cells (data not shown), unlike what was noted in mouse models, whereby limited IL-2 production was associated with increased IL-21 production by CD4 T cells (2,23). To ascertain whether IL-21-producing CD8 T cells manifested traits that resemble T follicular helper (Tfh) cells (24,25), we determined the frequency of IL-21-producing CD8 T cells that coexpressed Tfh-associated markers CXCR5 and inducible costimulator (ICOS).…”
contrasting
confidence: 52%
“…Recent observations have shown that IL-21 was able to rescue CD8 T cells cultured under IL-2 deprivation conditions. In these studies, blockade of both IL-2 and IL-21 signaling pathway led to reduced CD8 T cell survival (38). Similarly, in another study, IL-21 alone promoted expansion and cytolytic development of OT1 T cells (39).…”
Section: Discussionmentioning
confidence: 99%